2008
DOI: 10.1007/s00442-008-1095-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the predator complex of Homalodisca vitripennis (Hemiptera: Cicadellidae): a comparative study of the efficacy of an ELISA and PCR gut content assay

Abstract: A growing number of ecologists are using molecular gut content assays to qualitatively measure predation. The two most popular gut content assays are immunoassays employing pest-specific monoclonal antibodies (mAb) and polymerase chain reaction (PCR) assays employing pest-specific DNA. Here, we present results from the first study to simultaneously use both methods to identify predators of the glassy winged sharpshooter (GWSS), Homalodisca vitripennis (Germar) (Hemiptera: Cicadellidae). A total of 1,229 arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 53 publications
0
53
0
1
Order By: Relevance
“…Homalodisca vitripennis (Germar), for example, consumes between 10 and 100 times its dry body-weight hourly (see Redak et al 2004). During such lengthy feeding episodes sharpshooters are exposed to a range of visual predators including jumping spiders (Salticidae), assassin bugs (Hemiptera: Reduviidae), lizards (Lopez et al 2003;Suttle and Hoddle 2006;Fournier et al 2008), and potentially insectivorous birds (Burger et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Homalodisca vitripennis (Germar), for example, consumes between 10 and 100 times its dry body-weight hourly (see Redak et al 2004). During such lengthy feeding episodes sharpshooters are exposed to a range of visual predators including jumping spiders (Salticidae), assassin bugs (Hemiptera: Reduviidae), lizards (Lopez et al 2003;Suttle and Hoddle 2006;Fournier et al 2008), and potentially insectivorous birds (Burger et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, as in previous work with molecular predation studies (de Leó n et al 2006a, Fournier et al 2008, we demonstrated the importance of including an internal control (28S ampliÞca-tion) for these types of molecular marker assays. The internal controls become even more important when working with tiny insects, as in the current study.…”
Section: Discussionmentioning
confidence: 63%
“…To conÞrm for the presence of genomic DNA, ampliÞcation reactions were performed with 1 l of stock DNA and 28S primers at an annealing temperature of 65ЊC (forward, 5Ј-CCCTGTTGAGCTTGACTCTAGTCT-GGC-3Ј and reverse, 5Ј-AAGAGCCGACATCGAAG-GATC-3Ј) (Werren et al 1995) with 1.5 mM MgCl 2 and the ampliÞcation conditions described below. The 28S assay was also used as an internal control in subsequent PCR reactions to test for the presence of PCR inhibitors or failures (Pooler et al 1997, Vega et al 1993, de Leó n et al 2006a, Fournier et al 2008.…”
Section: Detection Of Parasitism and Time Of Detection Experimentsmentioning
confidence: 99%
“…При исследовании хищников цикады Homalodisca vitripenni ПЦР-анализ обходился в 7,5 дол-лара США на образец (стоимость праймеров не приво-дится), серологический анализ стоил 0,5 доллара США за образец, но на разработку антител потребовалось 12000 долларов США и год времени (Fournier et al, 2008). Там же приводится ссылка на исследователей, по-другому оценивающих ПЦР и серологический анализ (0,28 и 0,21 доллара соответственно) (Chen et al, 2000).…”
Section: сравнение пцр и серологического анализаunclassified